Existence and uniqueness theorem for a solution of fuzzy differential equations - Jong Yeoul Park; Hyo Keun Han (International Journal of Mathematics and Mathematical Sciences)
By using the method of successive approximation, we prove the existence and uniqueness of a solution of the fuzzy differential equation x′(t)=f(t,x(t)),x(t0)=x0. We also consider an ϵ-approximate solution of the above fuzzy differential equation.